THE SUITABILITY OF BLACK SOLDIER FLY LARVAE COMBINED WITH A COMMERCIAL DIET ON GROWTH AND FEED PERFORMANCES OF HYBRID CATFISH - Sirirustananun, Nuttarin; Saenthumpol, Rattanakorn; Chantarat, Thammasart (Indonesian Aquaculture Journal, 2023)
This study aimed to investigate the suitability of black soldier fly larvae (BSFL) combined with a commercial diet (CMD) on growth and feed performances of hybrid catfish (Clarias gariepinus x C. macrocephalus). A completedly randomized design was used to consist of four treatments and three replications with 100:0 (control), 75:25, 50:50, and 25:75 of CMD and fresh BSFL blended feeding. Fish were reared in 2 m2 inland canvas cages for 60 days. The results indicated that fish were fed 100% CMD had better average weight gain (AWG), daily weight gain (DWG), specific growth rate (SGR), food conversion ratio (FCR), feed efficiency (FE), and survival rate (SR) than the other treatments, but there was no statistically significant difference (p>0.05) when compared to 75:25 and 50:50 CMD:BSFL feeding. At the end of the experiment, the SR of fish was 81-91% and showed no significant difference (p>0.05) when compared between treatments. Therefore, hybrid catfish rearing can compensate CMD by fresh BSFL up to 50% of the feed amount per day. However, feeding with fresh BSFL can have side effects concerning steatosis